P763 Addiction in IBD patients: more than just smoke?. (25th January 2019) - Hirschmann, S; Koehnen, J; Schuster, B; Atreya, R; Krauss, N; Mudter, J; Dauer, M; Hagel, A; Neurath, M F; Albrecht, H
Abstract: Background: inflammatory bowel disease (IBD) represents a variety of chronic conditions, which may significantly impair the life of affected patients. Addictive behaviour of patients with IBD might significantly influence therapeutic outcome directly and indirectly. Hitherto, however, there exists no structured data about IBD and addiction. Objective of this study was to evaluate if patients with IBD are at higher risk for addictions. Moreover, to support the development of evidence-based tools aiming for improved medical assessment and hereby enable physicians to improve their therapeutic strategies. Methods: In this prospective multi-centre cross-section analysis, patients with IBD at six specialised IBD departments in Germany were asked to fill out a paper based self-reported anonymous questionnaire with 87 questions covering validated screening tests for the six most common addictions in Germany (alcohol, nicotine, drugs and illegal drugs, gambling, food). Furthermore, current treatment and clinical disease activity, measured by PRO 3-Score, were documented as well. Results: 191 patients (92 males, 99 females; mean age 39.0 years (SD 14.0), range 19–69 years) filled out the questionnaire between March and November 2018. Addictive behaviour could be determined at 61 of the 191 patients. The predominant share of these were regular smokers (27.7%), followed by high-risk drinkers (4.2%). 0.5% of the patients showed a severe level of drug abuse, 4.7% were classified as drug abusers on a moderate level. Another 0.5% of the patients were food dependent and 4.7% were at risk of food dependency. There have been no compulsive gamblers. Comparing these results with the general population, a significant higher proportion of IBD patients showed addictive behaviour for nicotine ( p = 0.049). IBD patients with addictive behaviour showed no significantly higher clinical disease activity based on calculation of the PRO 3-score compared with patients without any addictions. Patients with Crohn's disease were significantly more frequently smokers compared with patients with ulcerative colitis ( p = 0.004; smoking in 35.7% of the patients with Crohn's disease vs. 12.3% of the patients with ulcerative colitis). Conclusions: Addictive behaviour is not significantly more frequent in patients with IBD compared with the general population except of nicotine abuse. This addiction is significantly more prevalent among patients with Crohn's disease compared with patients with ulcerative colitis. Taking these results into account, qualified screening measures—particularly smoking assessment—should be implemented in daily practice, especially since addictions do not seem to be associated with higher self-reported disease activity.